Electrophysical Methods of Hydrocarbon Gases Conversion; 13 International symposium on high current electronics - Remnev G. E. Gennady Efimovich; Pushkarev A. I. Aleksandr Ivanovich; Kondratiev N. A.; Medvedev U. V. (Pulsed power applications, 2004)
Title from the title-page.